Tata Motor's transformational resource acquisition path: A case study of latecomer catch-up in a business group context - Gert Bruche (Hochschule für Wirtschaft und Recht Berlin, IMB Institute of Management Berlin, 2010)
In the mid 1990s India's Tata Motors Ltd. entered the passenger car business after having prospered for more than 40 years as a manufacturer of commercial vehicles. Based on archival data and on expert interviews the paper analyses the resource acquisition and internationalisation strategies and processes of this latecomer firm which has evolved in only 15 years from an initial entrant into a medium-sized passenger car manufacturer. The case reveals a pattern of top-down driven overlapping strategic initiatives in a catch-up process which combine external international resource acquisition with internal capability building and deliberate learning and upgrading processes. As Tata Motors is an affiliate of India's largest private business house, the Tata Group, the case study examines in a second part the role of group affiliation in the catch-up process. It is found that Tata Motors' rapid resource acquisition and creation process has been supported by dynamic group level capabilities, significant central group support and resource sharing across group companies; without the affiliation advantage the much accelerated catch-up process would not have been possible. The case contributes to the on-going debate about latecomer firms (or emerging multinationals or challenger firms) and suggests to undertake further studies on the question which role business group affiliation plays in the catch-up and internationalisation processes of firms from emerging economies. – – Nach mehr als vierzig Geschäftsjahren als Indiens führender LKW-Hersteller stieg Tata Motors Ltd. gegen Mitte der 1990er Jahre in das PKW-Geschäft ein. Auf der Basis einer umfangreichen Sammlung von Datenmaterial aus verschiedenen Quellen und von Experteninterviews untersucht die vorliegende Fallstudie den Ressourcen- und Fähigkeitsaufbau eines Nachzügler-Unternehmens, das sich in nur 15 Jahren zu einem mittelgroßen Automobilhersteller entwickelt hat. Die Studie zeigt einen Top-Management-getriebenen Aufholprozess der in überlappenden strategischen Projekten verläuft, wobei externe internationale Technologieakquisition mit internem Kompetenzaufbau und bewussten Lern- und Modernisierungsprozessen kombiniert wird. Da Tata Motors zur Tata-Gruppe - Indiens führender privater Firmen-Gruppe - gehört, wird in einem zweiten Schritt die Rolle der Gruppenzugehörigkeit im Aufhol- und Internationalisierungsprozess von Tata Motors untersucht. Die Studie zeigt, dass der Ressourcenaufbau durch dynamische Fähigkeiten auf zentraler Ebene, Zentralfunktionen und Ressourcenbereitstellung anderer Gruppengesellschaften unterstützt wurde und dass der Aufholprozess in dieser Geschwindigkeit ohne Gruppeneinbettung nicht möglich gewesen wäre. Die Fallstudie versteht sich als Beitrag zur Diskussion über die neuen multinationalen Firmen aus den Schwellenländern (die neuen Herausforderer wie sie in der deutschen Presse genannt werden) und zur Frage, welche Rolle die Gruppenzugehörigkeit oder konglomerate Einbettung im Aufhol- und Internationalisierungsprozess dieser Firmen spielen.
Keywords: 650